THE ROLE OF TOURIST VILLAGE COMPETITIVENESS FACTORS ON TOURISTS' BEHAVIORAL INTENTIONS - Hepy Hefri Ariyanto; Jacky Wijaya; Dame Afrina Sihombing (Journal of Management Small and Medium Enterprises (SMEs), 2026)
Research on the competitiveness of tourist villages from the perspective of tourists in Indonesia remains limited, despite the government’s strong commitment to developing tourist villages as instruments for economic growth, community welfare improvement, poverty alleviation, unemployment reduction, environmental conservation, and cultural preservation. This study investigates the competitiveness factors of tourist villages that influence tourists’ behavioral intentions, specifically their intention to visit or revisit and to recommend these destinations. The study is based on survey data collected from 318 respondents in Batam who have previously visited tourist villages. The findings indicate that overall competitiveness factors significantly affect tourists’ intentions to visit and recommend tourist villages. However, cultural and attractiveness-related factors do not significantly influence the intention to visit. These results provide important insights for tourist village managers and policymakers in designing strategies to strengthen destination competitiveness and stimulate positive tourist behavioral responses. The study contributes to the literature on destination competitiveness and sustainable rural tourism development in emerging economies. Keywords: Intention to Visit; Intention to Recommend; Destination Competitiveness; Tourist Village